(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women today are progressing in each field of society and are making a mark for themselves as doctors, lawyers, painters, singers, politicians, scientists and every other field. The concern however is that this number is very low and while they do enter the active workforce in large numbers a very insignificant number manages to break the glass ceiling. Further, while the number of educated women keeps going up, we also witness a sharp rise in reported and unreported cases of crime and abuse against women in their homes, workplace and in the society with the women not feeling empowered enough to stand up for their rights and defend themselves. Are we providing the right education to our women and is education the sole determinant of an empowered woman?